Acoustic effects of the reconstructed lateral epitympanic wall in a temporal bone and clinical study. (2nd August 2016) - Gostian, Antoniu‐Oreste; Schwarz, David; Pazen, David; Anagiotos, Andreas; Ortmann, Magdalene; Hüttenbrink, Karl Bernd; Beutner, Dirk
Abstract : Objective: Acoustic evaluation of reconstruction of the lateral epitympanic wall with bone or cartilage in a temporal bone study, and evaluation of audiometric data of patients who underwent cholesteatoma surgery with reconstruction of the lateral epitympanic wall with horseshoe‐shaped cartilage. Study Design: Temporal bone study and retrospective chart review. Methods: Preparation of temporal bones included reconstruction of the epitympanic wall with fixated and loose cartilage and bone. The volume velocities of the stapes footplate were measured from the inner‐ear side of the footplate by laser scanning doppler vibrometry following sound stimulation in the outer ear canal. Additionally, the audiometric data of 13 consecutive patients who underwent epitympanic cholesteatoma surgery, with an intact ossicular chain and reconstruction of the scutum with a horseshoe‐shaped cartilage in contact with the malleus' neck, were evaluated retrospectively. Results: The experimental results showed similar volume velocities at the stapes footplate for the fixated and unfixated cartilage as well as for the unfixated bone. However, the fixated bone yielded significantly reduced volume velocities. Clinical data confirmed that the cartilaginous horseshoe‐ technique allowed for a stable reconstruction of the scutum with satisfying audiometric outcome. Conclusion: In case of cholesteatoma surgery and the need for the reconstruction of the scutum, no adverse effects on hearing outcome are to be expected by using the malleus' neck as an anchoring point for cartilaginous scutum reconstruction. Level of Evidence: NA. Laryngoscope, 127:1427–1434, 2017